The Kinetics of n‐Butyl Acrylate Radical Polymerization Revealed in a Single Experiment by Real Time On‐line Mass Spectrometry Monitoring - Haven, Joris J.; Zaquen, Neomy; Rubens, Maarten; Junkers, Tanja (Macromolecular reaction engineering, 2017)
The high‐temperature trithiocarbonate‐mediated reversible addition–fragmentation chain transfer (RAFT) polymerization of n‐butyl acrylate is studied using a high‐resolution mass spectrometric on‐line monitoring method. Therefore, an Orbitrap mass spectrometer, ideally suited for polymer analysis, is coupled to a continuous flow microreactor. Via adjustment of flow rates in the reactor, time sweep experiments can be carried out to allow monitoring a whole polymerization in a single experiment. The n‐butyl acrylate polymerization is monitored in a temperature interval between 100 and 190 °C for reaction times between 1 and 10 minutes. In all cases, full monomer conversions are reached and even at the highest temperatures still relatively good molecular weight control and reasonably low dispersities are obtained. End group analysis from mass spectrometry reveals, however, that the desired RAFT product is already at the lower temperatures less abundant than some side products. The herein described on‐line monitoring technique gives access to quasi‐continuous data acquisition, and is found to be very robust, and low in scattering when compared to classical batch sampling techniques. Microreactor technology in combination with mass spectrometry monitoring allows for on‐line “nonstop” analysis. The kinetics of n‐butyl acrylate polymerizations via reversible addition–fragmentation chain transfer polymerization are investigated for a wide range of microreactor temperatures and residence times.